(untitled) - Trương, Thụy Thiên Hương (Can Tho, 2009)
This study aimed to find out the impact of using language games as warm-up activities on students' short and long-term vocabulary retention and their motivation, the correlation between students' motivation and their vocabulary retention, and the students' attitude towards using language games for vocabulary revision in the warm-up stage.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu